Bl-RADS lexicon: An urgent call for the standardization of breast ultrasound in Nigeria (2005)
Ultrasound technology and its ability to demonstrate breast anatomy and pathology has changed dramatically and rapidly in the last decade, sonography is now utilized to characterize and manage palpable and mammographic abnormalities. It is also useful in evaluating nipple discharge and mammary implants. Breast ultrasound (BUS) is on invaluable tool for assessing the extent of malignant disease and regional lymph nodes is also available for evaluation of the breast after breast cancer treatment. All of the above have encouraged the development of Bl-RADS ultrasound to further improve and standardize Breast Sonography. This Lexicon is being presented to radiologists, breast surgeons, breast oncologists, breast pathologists, and breast sonographers.